The first checklist of alien vascular plants of Kyrgyzstan, with new records and critical evaluation of earlier data. Contribution 2 - Alexander Sennikov; Georgy Lazkov (Biodiversity Data Journal, 2022)
We continue the inventory of alien vascular plants of Kyrgyzstan, with emphasis on the time and pathways of introduction of the species and their current status in the territory. Each taxon is discussed in the context of plant invasions in Central Asia. This work is a further development of the preliminary checklist of alien plants of Kyrgyzstan, which was compiled for the Global Register of Introduced and Invasive Species in 2018.This contribution includes all alien species of Kyrgyzstan belonging to Solanaceae and Asphodelaceae and one species of Asteraceae. Physalis philadelphicus (syn. P. ixocarpa) is reported for the first time from Central Asia, as new to Kazakhstan, Kyrgyzstan and Uzbekistan, thus marking a recent invasion with a variety of imported grain and seed material. The old records of P. ixocarpa from Uzbekistan are based on misidentified specimens of P. angulata. Physalis angulata is an old cotton immigrant in Central Asia, whose invasion started in the 1920s; it is excluded from the alien flora of Kyrgyzstan as registered in error on the basis of cultivated plants. Alkekengi officinarum is an archaeophyte of the Neolithic period in Central Asia, formerly used for food, now strongly declining and largely casual in Kyrgyzstan. The only historical record of Physalis viscosa from Uzbekistan was based on a technical error and belongs to A. officinarum. Datura stramonium and Hyoscyamus niger were introduced as medicinal plants during the period of the Arabic invasion of Central Asia, by the 11th century. Datura innoxia is a newly recorded casual alien, recently escaped from ornamental cultivation. Nicandra physalodes is a casual alien, which was cultivated by Russian colonists in the early 20th century for culinary use and is currently used in ornamental cultivation. Hemerocallis fulva was a remnant of historical cultivation in the former Khanate of Buxoro, and its formerly established colonies are presumably extinct in the wild. Bidens frondosa was seemingly introduced with contaminated forage and seed of American origin during the late Soviet period and started to spread in the period of independence; its invasion in the former USSR is analysed.